A multispecialty ethnographic study of clinical competency committees (CCCs). (2nd November 2022) - Ekpenyong, Andem; Edgar, Laura; Wilkerson, LuAnn; Holmboe, Eric S.
Abstract: Purpose: Clinical competency committees (CCCs) assess residents' performance on their specialty specific milestones, however there is no 'one-size fits all' blueprint for accomplishing this. Thus, CCCs have had to develop their own procedures. The goal of this study was to examine these efforts to assist new programs embarking on this venture and established programs looking to improve their CCC practices and processes. Methods: We purposefully sampled CCCs across multiple specialties and institutions. Data from three sources were triangulated: (1) online demographic survey, (2) ethnographic observations of CCC meetings and (3) post-observation semi-structured interviews with the program director and/or CCC chairperson. Template analysis was used to build the coding structure. Results: Sixteen observations were completed with 15 different CCCs at 9 institutions. Three main thematic categories that impact the operations of CCCs emerged: (1) Membership structure and members roles, (2) Roles of the CCC in residency and 3) CCC processes, including trainee presentation to the committee and decision-making. While effective practices were observed, substantial variation existed in all three thematic areas. Conclusions: While CCCs used some known effective practices, substantial variation in structure and processes was notable across CCCs. Future work should explore the impact of this variation on educational outcomes.